Efficient Mechanisms for Access to Storage with Imperfect Competition in Gas Markets - Alberto Cavaliere; Valentina Giust; Mario Maggi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
Scarce storage capacity and distortions in access to gas storage are considered causes of market foreclosure in liberalized gas markets. We consider rules currently adopted in Europe for storage rationing and propose efficient rationing mechanism based on the value of storage, when other flexibility inputs are available. Firstly we analyse productive efficiency issues neglecting vertical restraints and strategic behaviour in the final market. Then we assume imperfect compettion in the downstream market for gas supplies, given the avaialbility of storage capacity upstream. We consider effciency issues in a two stage model comparing regulated storage tariffs coupled with a centralizedrationing mechanism with storage auctions. Finally we consider as an optimal mechanism the allocation of storage arising from welfare maximization by a social planner. We find that it is usually optimal to maximize the amount of storage capacity allocated to new entrants in the gas markets. Storage auctions deviates from the optimal mechanism, but still improve efficiency, with respect to current mechanisms, to the extent that they allocate storage according to its value. Furthermore storage allocation appear to be an extremeley powerful mechanism to improve competition and efficiency in gas markets.
Keywords: L51; L95; D45; 330; Liberalization; Auctions; Essential Facilities